A diffusion-weighted MRI study of acute ischemic distal arm paresis - Gass, Achim; Szabo, Kristina; Behrens, Stephan; Roßmanith, Christina; Hennerici, Michael G. (Neurology, 2001)
Objective: To study the site of the ischemic lesion, the underlying cause, and the prognosis of acute stroke with distal arm paresis. - Method: The authors investigated 14 consecutive patients with acute distal arm paresis with a diagnostic stroke protocol and early MRI, including T2-weighted images, diffusion-weighted images (DWI), and perfusion-weighted images (PWI). Acute DWI lesions were shown on coregistered T2-weighted images for analysis of the exact anatomic lesion location. - Results: Patients showed a uniform (7/14), radial (3/14), or ulnar (4/14) distribution of hand paresis. In all cases, DWI identified small lesions located in the motor cortex. Topographic lesion analysis, which was correlated with the clinical deficit, showed lesions centered in the hand knob area (2/14), involving the lateral (6/14), medial (4/14), or both (2/14) borders of the hand knob. PWI (calculated time-to-peak maps) did not show a mismatch between the DWI lesion and the PWI lesion. In six patients, DWI and PWI lesions were identical in size and location; no definite perfusion deficit was seen in eight patients. In agreement with PWI, no patient showed clinical worsening, and six patients recovered completely within a week. Further investigations showed a potential source of embolus in 11 cases. - Conclusions: Acute ischemic distal arm paresis is usually caused by a small cortical lesion in the motor hand cortex attributable to distal Rolandic artery obstruction without additional tissue at risk. These findings confirm the observed benign clinical course and its apparent main cause (artery-to-artery or cardiac embolism).